Bandwidth Enhancement of Microstrip Antenna with Corner Truncation for UWB Application Using Cavity Model Analysis - Laxmi Prasad Mishra, Swarnaprava Sahoo (International Journal of Advanced Science and Technology, 2020)
Bandwidth improvement of microstrip antenna with corner truncation and equivalent circuit approximate using cavity model analysis for UWB application is presented. Pair of corner truncation and an U- slot are incorporated in the rectangular radiating element for bandwidth improvement. The truncated corners and slot dimensions are the major factors of impedance bandwidth. The proposed antenna covers impedance bandwidth of 105.5% from 3.4 GHz to 11 GHz with maximum gain 5.9 dBi and efficiency 97.90%. The proposed antenna is compared with the microstrip patch antenna (without U-slot truncated corner) and other parameters are also studied. The theoretical, simulated and experimental results are compared with well agreement.